Propuesta de mejoramiento del proceso de microcrédito del programa círculos de economía solidaria (CESOL) - Cuesta Flores, Geoconda Lucía (2006)
In such circumstances, the present work allows an approach to the reality that unfolds the Circles Program Solidarity Economy (CESOL) microcredit program run by the YMCA Ecuador, with the aim of developing improved work process microcredit program in question, in order to strengthen the program